A new species of Ptomaphagus (Appadelopsis) (Coleoptera: Leiodidae) from Great Smoky Mountains National Park, U.S.A. - Tishechkin, Alexey K. (Zootaxa, 2007)
Recent activities within the beetle component of the Great Smoky Mountains National Park (GSMNP) All-Taxa Biodiversity Inventory (ATBI) include a substantial collecting effort (Carlton & Bayless in press). Sampling of forest litter-dwelling beetles is an important part of this collecting program, and substantial numbers (217 by the end of 2006) of samples from GSMNP and vicinity has been processed since 2001. The progress of sorting and identification of this material varies depending on taxon, but several new species have been discovered and described (e.g., Konstantinov & Tishechkin 2004; Sokolov et al. 2004; Gimmel & Ślipiński 2007). This paper is the first taxonomic treatment of the genus Ptomaphagus Illiger, 1798 subgenus Appadelopsis Gnaspini, 1996, of the Great Smokies.